The in-silico potential of Andrographis paniculata phytocompounds as antiviral for the treatment of COVID-19: A systematic review - Shafa Shavira, Septi Handayani, Fatmaria Fatmaria (Journal of Applied Pharmaceutical Science, 2023)
Since the outbreak of coronavirus disease 2019 (COVID-19), many studies have been conducted to develop definitive therapeutic agents for this viral disease. The in-silico method has become the best solution for the initial step in discovering potential antiviral compounds. Several phytocompounds from a medicinal plant, Andrographis paniculata, were reported to have activity inhibiting SARS-CoV-2 proteins. The present systematic review aims to determine the potency of A. paniculata compounds against COVID-19. We undertook a systematic search in two databases, PubMed and Google Scholar, and included original articles that applied in-silico methods for phytocompounds of A. paniculata in COVID-19. Twenty-nine original articles were included in the systematic review. We report that 50 of the 107 A. paniculata phytocompounds (46.73%) were against SARS-CoV-2. We found that five protein targets of SARS-CoV-2 are highly conserved structures mostly used in the articles, which are main protease, papain-like protease, RNA-dependent RNA polymerase, Nsp15, and spike protein. Six A. paniculata phytocompounds have an inhibition activity of those five protein targets including andrographolide, neoandrographolide, isoandrographolide, 14-deoxyandrographolide, 14-deoxy-11,12-didehydroandrographolide, and andrographidin C as main diterpenoid compounds. Based on the literature evidence, some of the A. paniculata phytocompounds could be potential antiviral agents due to their strong binding affinities and stable conformations toward SARS-CoV-2 proteins.